1999
DOI: 10.1007/s002130050835
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of the tryptophan depletion method

Abstract: Thirteen healthy subjects were subjected to tryptophan (TRP) depletion, lysine (LYS) depletion, and a placebo condition in a double blind cross-over study. The aim of the study was to test the specificity of psychological effects induced by TRP depletion. Subjects ingested a 100 g amino acid mixture with or without TRP or LYS. Six hours later, plasma TRP levels had decreased by 77% in the TRP depletion test and LYS levels by 51% in the LYS depletion condition. After 6 h of TRP depletion, subjects reported sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 33 publications
0
45
1
Order By: Relevance
“…Given that these amino acids are present in the same amounts in TRP-free and TRP-containing preparations, and that sham depletion techniques have measurable effects only rarely, the discrepancy between the effects seen with TRP-free and TRP-containing challenges therefore cannot be accounted for by simply having taken in a huge bolus of amino acids. In support of this, Klaassen et al (1999a) depleted healthy subjects either of TRP or lysine, using a similar preparation. Unlike RTD, rapid lysine depletion provoked no measurable mood or memory effects.…”
Section: Are There Non-serotonergic Explanations For the Effects Of Rtd?mentioning
confidence: 76%
“…Given that these amino acids are present in the same amounts in TRP-free and TRP-containing preparations, and that sham depletion techniques have measurable effects only rarely, the discrepancy between the effects seen with TRP-free and TRP-containing challenges therefore cannot be accounted for by simply having taken in a huge bolus of amino acids. In support of this, Klaassen et al (1999a) depleted healthy subjects either of TRP or lysine, using a similar preparation. Unlike RTD, rapid lysine depletion provoked no measurable mood or memory effects.…”
Section: Are There Non-serotonergic Explanations For the Effects Of Rtd?mentioning
confidence: 76%
“…For example, a growing body of literature has demonstrated that tryptophan depletion is associated with decrements in cognition in samples of healthy controls (Evers et al 2005;Klaassen et al 1999;Murphy et al 2002). One study showed that manipulation of tryptophan levels in abstinent MDMA users is associated with altered performance on a memory test (Curran and Verheyden 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical and physiological consequences of ATD can be followed over a period of several hours. After the intervention, tryptophan levels quickly return to normal upon return to a normal diet (Klaassen et al, 1999b).…”
Section: Amino-acid Mixturesmentioning
confidence: 99%
“…The preparation and composition of the amino-acid mixture was the same as described by Klaassen et al (1999b) and Riedel et al (1999) In the active condition, 3 g/100 g tryptophan was left out. Apart from the amino acids, the mixture contained 63 g carbohydrates and 33 g fat in order to dissolve the amino acids and provide caloric value.…”
Section: Amino-acid Mixturesmentioning
confidence: 99%